IMPLEMENTATION OF SERVICES AT PT. ARAS HIJRAH TOUR AND TRAVEL IN PEKANBARU - Tri Wahyuni; Febri Yuliani (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2023)
ABSTRACT This study aims to determine the implementation of services at PT. Aras Hijrah Toutr And Travel In Pekanbaru. Tangible, Empathy, Reliability Responsiveness and Assurance. This study uses a qualitative method with a qualitative descriptive approach to describe and explain the circumstances that occur by collecting data and information in the field. The key informants in this study are the Main Director, Employees and Customers. In this study, the data collection techniques used were interviews, observation and documentation. Based on the results of the study, it can be concluded that having uniforms is mandatory, providing comfortable waiting rooms, prioritizing service, providing services in good language, providing solutions and providing good facilities for customers. Keywords: Implementation, service, PT. Aras Hijrah Tour And Travel